Managing literacy interventions through professional learning communities: a case study on organizational change in education systems - Marianne Hunt; Yuyang Yan; Blanca Meyer; Hui Liu (Humanities & Social Sciences Communications)
Abstract This mixed-method case study explores the implementation and impact of a grade-wide literacy intervention program through a professional learning community (PLC) at a middle school in Norwalk, California. A team of sixth-grade teachers who had adopted the principles of DuFour, Fullan and Quinn sought to create a PLC that could lead to positive change in school culture and literacy rates across the curriculum. The research questions are: What does a systemic grade-wide literacy-focused PLC intervention look like? What is its impact on reading comprehension, literacy practices, and student confidence? How does this effort influence the school system and stakeholder buy-in? Data was collected through pre- and post-surveys from students and staff, meeting agendas, notes, and correspondences, along with i-Ready scores to measure reading comprehension growth. Initially, 103 students were reading below the fourth-grade level; by the end of the year, this number decreased by 18.4% to 84 students. Surveys and reflections indicated improved teacher-student relationships, with students feeling more supported. Additionally, students exhibited positive literacy practices and increased confidence as readers. The initiative positively impacted the wider school culture, leading other grade-level teams to adopt similar practices. This study highlights the managerial and organizational benefits of PLCs in educational settings.